2011
DOI: 10.3152/030234211x12834251302445
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for career and mobility of researchers in Europe

Abstract: Career development and mobility of highly skilled people have been at the centre of several fora and actions in Europe. Research and policy representatives have investigated which are the motivating and inhibiting factors for international mobility, which are the conditions and problems that researchers face in their work and career development, and how to foster creativity, knowledge creation and innovation. This paper is based on a survey carried out within the E*CARE project of the EU's Seventh Framework Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Studies of academics depict that their mobility choices are mostly kindled by the reputation of host HEIs, the research resources at their disposal and the compatibility between the job post and their research preferences (Agarwal & Ohyama, 2013;De Grip, Fouarge & Sauermann, 2010;Ivancheva & Gourova, 2011). Williams and Omar (2014) argue that the running and effectiveness of HEIs are vastly associated with the quest for prestige or reputation.…”
Section: Literature Review Factors Affecting the Organisational Brandmentioning
confidence: 99%
“…Studies of academics depict that their mobility choices are mostly kindled by the reputation of host HEIs, the research resources at their disposal and the compatibility between the job post and their research preferences (Agarwal & Ohyama, 2013;De Grip, Fouarge & Sauermann, 2010;Ivancheva & Gourova, 2011). Williams and Omar (2014) argue that the running and effectiveness of HEIs are vastly associated with the quest for prestige or reputation.…”
Section: Literature Review Factors Affecting the Organisational Brandmentioning
confidence: 99%
“…The researchers indicated that the possibility for future career development, working on an interesting research topic and participation in a collaborative research project were among the most important motives for mobility, although the reputation of the host institutions also plays a significant role. Major obstacles for mobility are family and other personal connections, as well as the complex administration of relocation and lack of support from the home institution (Ivancheva and Gourova, 2011). De Grip et al (2009) study the factors that influence European science and engineering graduates to become internationally mobile right after their studies and 5 years later.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To reach the academic top, recruiting and keeping the best staff is crucial, as a critical mass of competent highly skilled people is decisive for excellence (Ivancheva and Gourova, 2011). Van den Brink (2009) describes 'recruiting the best scholars' as the core business of universities.…”
Section: Introductionmentioning
confidence: 99%